Peran Kepolisian dalam Penyidikan Tindak Pidana Pembunuhan pada Unit Reserse Polsek Sipispis - Bringin Jaya; Marlina Marlina; Rizkan Zulyandi (Mahesa Research Center, 2021)
Criminal acts that result in the death of a person often occur. In general, proving the existence of death in this type of crime is not difficult, because a person's death can be proven from the presence of medical information which states that someone is dead. The legal arrangements regarding the role of the police in investigating murder crimes are as follows: In the preamble to Law of the Republic of Indonesia Number 2 of 2002 concerning the National Police of the Republic of Indonesia, in letter b, it is stated that maintaining domestic security through efforts to carry out police functions which include maintaining security and public order, law enforcement, protection, protection, and services to the community, the implementation of the role of the criminal police investigation team in uncovering the crime of murder is: Investigation Stage An investigator in carrying out his duties has legal corridors that must be obeyed and regulated formally. what and how to perform, the tasks in the investigation. Obstacles and obstacles to investigation that come from within the Police can include: (i) job irregularities, and (ii) abuse of authority, while obstacles and constraints to the Police Research Unit (Internal Constraints) are (i) inaccurate or careless about an object, (ii) Lack of facilities and infrastructure.